Detoxification of inorganic contaminants in transgenic Arabidopsis thaliana - Mohammed, Raghad; Ibrahim, Kadhim; Ali, Norrya; Al-Daoude, Antonious (Al-Nahrain Journal of Science, 2017)
In detoxification, the plant takes up the contaminant of concern from soil, water, or a mixture of both, converts it to a volatile form, and releases it to the atmosphere, usually through the leaf stomata. This technique is only suitable for contaminants that do not pose a significant air pollution hazard. Contaminants taken up by the roots pass through the roots to the leaves and are volatized through stomata where gas exchange occurs. This experimental work examines the ability of transgenic Arabidopsis thaliana with P4502E1 gene from rabbit to detoxify for many soil contaminants. The P450 2E1 enzyme controls the rate-limiting step in the metabolism of multiple environmental pollutants. The percentage of transformation increased at the less diluted cultures of Agrobacterium tumefaciens. The ability of transgenic plants were tested for their potential in remediation of metals such as Sodium (Na), Magnesium (Mg), Potassium (K), Calcium (Ca), Manganese (Mn), Iron (Fe), Copper (Cu), Zinc (Zn), and Nickel (Ni). In the present work, transgenic plants were more efficient achieving 31, 46, 42, 48, 33, 51, 35, 29 and 39% contribution of each to the total value of detoxification contaminants.